Malthus en zijn bevolkingswet - Fraiture, Armand (Brussel : De Wilde Roos, 1928)
Collectie Vrijzinnige Werkmansbibliotheek
Nederlands
Monografie
Keywords: Malthus, Thomas; Vrijzinnige Werkmansbibliotheek; malthusianisme